STRATEGI KIYAI DALAM MENANAMKAN NILAI-NILAI NASIONALISME DI PONDOK PESANTREN - Iswiyanto, Hendra Ani (Al-Rabwah, 2024)
This research aims to analyze and provide an interpretation of the values of nationalism in Islamic boarding schools, the Kiyai's strategy for instilling nationalist values in Islamic boarding schools, and the obstacles to instilling nationalist values in Islamic boarding schools. The method used in this research is a qualitative approach with a case study type. This research was conducted at the Hidayatullah Balikpapan Islamic Boarding School Foundation. There were 10 informants in this research. The results show that the values instilled include the values of piety, unity, justice, solidarity, responsibility, loyalty, mutual help, peace, tolerance, and historical values. The strategies used to instill nationalist values are education, habituation, and example. The obstacles to instilling values at the Hidayatullah Balikpapan Islamic boarding school are limited resources, funds, and facilities; minimal access to training for teachers to be trained in integrating nationalist values into the curriculum; books about nationalism are still limited; facilities and infrastructure are still limited; and they receive less attention and support from the government. It is hoped that this research will provide benefits in developing nationalist values at the Hidayatullah Balikpapan Islamic Boarding School and also as a guide for Islamic educational institutions and the wider community in understanding nationalist values in the context of multicultural Indonesia